Structure, luminescence of Eu2+ and Eu3+ in CaMgSi2O6 and their co-existence for the excitation-wavelength/temperature driven colour evolution. Issue 29 (24th June 2021) - Su, Fang; Zhou, Weijie; Yang, Yunlin; Ou, Yiyi; Qi, Zeming; Duan, Chang-Kui; Brik, Mikhail G.; Dorenbos, Pieter; Liang, Hongbin
Abstract : The structure, luminescence and valence stabilities of Eu 2+/3+ -doped CaMgSi2 O6 are studied. The varied luminescence colour responses to the temperature and excitation wavelengths endow their potential application in anti-counterfeiting. Abstract : Luminescent materials with controllable colour evolution features are demanded for the development of multi-level anti-counterfeiting technologies. Here we report the structural and luminescence properties of CaMgSi2 O6 :Ln (Ln = Eu 2+, Eu 3+, Eu 2+/3+ ) samples in detail and reveal their excitation-wavelength/temperature driven colour evolution characteristics. By tuning either the excitation-wavelength (276, 304, 343, 394 nm) or temperature (in the 330–505 K range), the designed samples with co-existing Eu 2+ /Eu 3+ ions can achieve diverse and controllable colour evolution from red, to pink, purple and blue. This shows their potential application in anti-counterfeiting with the help of sophisticated pattern design. In addition, the underlying mechanism of the Stokes shift of the Eu 2+ emission and valence stability of both Eu 2+ /Eu 3+ ions in CaMgSi2 O6 are also studied in depth. These results are valuable for designing colour-controllable luminescent materials based on the co-existence of the Eu 2+ /Eu 3+ ions for anti-counterfeiting applications.